PERKEMBANGAN KAJIAN TEORITIS TAFSIR SOSIAL DI INDONESIA - Yusron, M. Agus (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
The Qur'an is a guide for humans, a guide in carrying out the mandate as caliph. So it is imperative to understand the meaning of the Qur'an, so as not to fall into error or misery. Its status as a human guide until the end of time requires scholars to practice ijtihad to find the right method or approach according to the times. In contemporary times, the approach or style of interpretation is developing very rapidly, one of which has been developed recently is the adab al-ijtima'i style, a style that emphasizes the social problems of society. This style tries to connect the verse text with the social context of the community, as an effort to overcome the problems that exist in the community, and its presentation in language that is easy to understand and interesting. The originators of this pattern are Jamaluddin al-Afghani, Muhammad Abduh, and Rashid Rida. In this study, it will be investigated how the development of theoretical studies of social interpretation in Indonesia. Starting from the era before independence, the old order, the new order, reform, to democracy. The attention of Indonesian scholars to the study of social interpretation is very rapid, there are books of interpretation that focus on efforts to overcome community problems, or writings that offer solutions to various community problems. Among the books or books that are quite familiar in Indonesia are the interpretations of Al-Mishbah, Al-Azhar, An-Nur, or in the form of simple books such as Oasis of the Qur'an, Tafsir on Social Media, or theses, theses, dissertations, to journals written by academics on Al-Qur'an campuses.